2004
DOI: 10.1016/j.nuclcard.2004.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of ECG-gated SPECT imaging in patients undergoing stress Tc-99m sestamibi myocardial perfusion imaging

Abstract: Ventricular function data from ECG-gated SPECT add important prognostic value to data obtained from perfusion imaging alone in predicting adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 29 publications
3
36
0
5
Order By: Relevance
“…Therefore, the main task of imaging procedures is to help in defining patient prognosis, identifying those subjects at risk for adverse events, mainly cardiac death or nonfatal myocardial infarction. As regards prognostication, several studies have examined the role of gated myocardial perfusion SPECT [85][86][87][88][89][90][91][92][93][94]. In general, the functional parameters improve the predictive models.…”
Section: Incremental Diagnostic Value Of Function Over Perfusionmentioning
confidence: 99%
“…Therefore, the main task of imaging procedures is to help in defining patient prognosis, identifying those subjects at risk for adverse events, mainly cardiac death or nonfatal myocardial infarction. As regards prognostication, several studies have examined the role of gated myocardial perfusion SPECT [85][86][87][88][89][90][91][92][93][94]. In general, the functional parameters improve the predictive models.…”
Section: Incremental Diagnostic Value Of Function Over Perfusionmentioning
confidence: 99%
“…Technetium-99m (Tc-99 m) methoxyisobutyl-isonitrile (MIBI) 1 or tetrofosmin 2 is considered the radionuclide of choice for left ventricular ejection fraction (LVEF) assessment by electrocardiogram (ECG) gated single photon emission computed tomography (SPECT). Compared with Tc-99 m labeled compounds, thallium-201 (Tl-201) is considered to possess poor image quality 3 -4 due to its lower photon energy and flux, resulting in increased scatter and attenuation.However,its better physiological propertiesand the recent development of new cameras based on semiconductor detectors like cadmium zinc telluride (CZT) have resulted in a renewed interest in the use of Tl-201 for cardiac perfusion imaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the SSS has been shown to be a powerful independent predictor of cardiac events. 10,[22][23][24] However, most of the observations have been made in a mixed gender population. 10,22-24 Sharir et al 11 showed that for CD and MI, perfusion data provided a larger proportion of the prognostic information for women than they did for men.…”
Section: Prognostic Value Of Perfusion Datamentioning
confidence: 99%
“…This is in line with previous findings that suggest that the extent of defect size and functional abnormalities are more predictive for hard events (CD and MI), whereas the extent of ischemia is more predictive for soft events and/or MI. 10,[25][26][27] By using gated SPECT perfusion imaging, women at increased risk of having a cardiac event could be identified.…”
Section: Prognostic Value Of Perfusion Datamentioning
confidence: 99%
See 1 more Smart Citation